Mirabilis jalapa L. atividade farmacológica e citotóxica - Walker, Cristiani Isabel Banderó (2007)
The family Nyctaginaceae consist of approximately 30 genus and 14 species. In Brazil, 10 genus and 70 species are found. The genus Mirabilis belongs this family and can be found spread worldwide. This plant popularly known as maravilha or bonina and it is used in folk medicine to treat infection, inflammation and pain. The plant was collected in March 2006 in Santa Maria (RS). Ethanolic extract (70%) was made by maceration and fractionated using organic solvents with increasing polarity (hexanic, dichloromethane, ethyl acetate and butanolic). Through qualitative chemical analysis it was found in greater quantity alkaloids, amino groups, sterols and/or triterpenoids, hidroxiantraquinones, anthocyanic pigments, volatile acids and phenols. In relation to the antimicrobial activity, the best response was obtained for the fraction dichloromethane from stem and the ethyl acetate from leaves for S. aureus and the fraction ethyl acetate from stem and leaves for S. cerevisiae. The higher concentration of phenolic compounds was found in the ethyl acetate fraction from leaves (7,45 mg/g drug). Through the method of DPPH, all samples showed antioxidant activity by TLC and by spectrophotometry. Ethyl acetate and butanolic fractions from leaves showed excellent antioxidant activity with IC50 of 20,40 μg/ml and 25,41 μg/ml, respectively. The highest content of quercetin was found in the leaves extract (0,19%). The ethyl acetate fraction produced analgesic activity reaching 82.8±7.9% inhibition in the writhing test. The hexanic fraction from leaves expressed the best toxicity front of Artemia (LC50 = 1.27 μg/ml)